2005
DOI: 10.1093/carcin/bgi365
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic oval cell response to the choline-deficient, ethionine supplemented model of murine liver injury is attenuated by the administration of a cyclo-oxygenase 2 inhibitor

Abstract: Oval cell proliferation precedes neoplasia in many rodent models of hepatocellular carcinoma and prevention of this proliferative response can reduce the risk of subsequent carcinoma. This study aimed to determine whether a selective cyclo-oxygenase-2 (COX-2) inhibitor, SC-236, affects (i) the oval cell response to liver injury in a mouse model of hepatocarcinogenesis and (ii) an oval cell line. Four-week-old mice were fed either normal chow or a choline deficient, ethionine supplemented (CDE) diet in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…Oval cell apoptosis has been shown to be mediated via Akt activity (Davies et al, 2006). We observed that a few oval cells stained positively for Bcl-2 and caspase 8 especially in the periportal areas.…”
Section: Brdu and Tunel Stainingmentioning
confidence: 61%
“…Oval cell apoptosis has been shown to be mediated via Akt activity (Davies et al, 2006). We observed that a few oval cells stained positively for Bcl-2 and caspase 8 especially in the periportal areas.…”
Section: Brdu and Tunel Stainingmentioning
confidence: 61%
“…LPCs are recognized as being highly heterogeneous and dynamic, and several previous studies from our laboratory have illustrated selective modulation of discrete subpopulations of LPCs by cytokines. 3,30,31 Because the LPC compartment induced in various liver injury models may be different, we aimed to further explore the role of the TWEAK pathway in an additional in vivo model of LPC expansion and to study its effects directly on LPC lines in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…As oval cellmediated liver regeneration is accompanied by an inflammatory response, these cytokines could play an important role. Inhibiting this response, by treating with dexamethasone or a cyclooxygenase 2 inhibitor, reduces the expansion of oval cells in the damaged liver (43,44).…”
Section: Discussionmentioning
confidence: 99%